MAKNA PEMBELAJARAN BAHASA INDONESIA BAGI SISWA GENERASI Z: RELEVANSI ATAU SEKADAR FORMALITAS DI TENGAH PENGARUH BAHASA GAUL DAN MEDIA SOSIAL - Nursalim; Marpaung, Syafaruddin; Dasmarni; Mairista, Missy (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of social media and the dominance of slang among Generation Z have transformed communication patterns and language practices among students in educational settings. This phenomenon raises questions about the meaning and relevance of Indonesian language learning in schools—whether it still holds substantive function or has become merely a curriculum formality. This study aims to analyze the meaning of Indonesian language learning for Generation Z students amid the influence of slang and social media, as well as to identify its implications for formal literacy competence. The research employs a qualitative descriptive approach using literature study and thematic analysis of national (Sinta-indexed) and international studies published in the last five years, strengthened by phenomenological observation of students’ language practices in digital media. The findings indicate that slang serves as a social identity marker and a means of self-expression for Generation Z. However, its intense use has the potential to affect the quality of formal language usage in academic contexts, particularly in grammar, sentence structure, and diction accuracy. Nevertheless, Indonesian language learning retains strategic relevance as a foundation for academic literacy, reinforcement of national identity, and development of contextual communicative competence. Therefore, there is a need for an integrative and adaptive transformation of teaching approaches based on digital literacy so that Indonesian language education is not perceived as a mere formality, but as an essential competence aligned with the needs of the digital generation.